Assessing species diversity of Coral Triangle artisanal fisheries: A DNA barcode reference library for the shore fishes retailed at Ambon harbor (Indonesia). Issue 7 (6th March 2020) - Limmon, Gino; Delrieu‐Trottin, Erwan; Patikawa, Jesaya; Rijoly, Frederik; Dahruddin, Hadi; Busson, Frédéric; Steinke, Dirk; Hubert, Nicolas
Abstract: The Coral Triangle (CT), a region spanning across Indonesia and Philippines, is home to about 4, 350 marine fish species and is among the world's most emblematic regions in terms of conservation. Threatened by overfishing and oceans warming, the CT fisheries have faced drastic declines over the last decades. Usually monitored through a biomass‐based approach, fisheries trends have rarely been characterized at the species level due to the high number of taxa involved and the difficulty to accurately and routinely identify individuals to the species level. Biomass, however, is a poor proxy of species richness, and automated methods of species identification are required to move beyond biomass‐based approaches. Recent meta‐analyses have demonstrated that species richness peaks at intermediary levels of biomass. Consequently, preserving biomass is not equal to preserving biodiversity. We present the results of a survey to estimate the shore fish diversity retailed at the harbor of Ambon Island, an island located at the center of the CT that display exceptionally high biomass despite high levels of threat, while building a DNA barcode reference library of CT shore fishes targeted by artisanal fisheries. We sampled 1, 187 specimens and successfully barcoded 696 of the 760 selected specimens that represent 202 species. Our results show that DNA barcodes were effective in capturing species boundaries for 96% of the species examined, which opens new perspectives for the routine monitoring of the CT fisheries. Abstract : The Coral Triangle is home of the highest marine biodiversity. Artisanal fisheries are extremely important in the Coral Triangle. Fish species are poorly known and hardly identifiable. We propose a DNA barcode reference library for the fish harvested by the artisanal fisheries in Ambon Island.